Synthesis, Acaricidal, Bacteriostatic Activity Among the Amino Derivatives 5,7-Dichloro-4,6-Dinitrobenzofuroxana - L. V. Spatlova (Разработка и регистрация лекарственных средств, 2019)
Introduction. In recent years, interest in the compounds of the benzofuroxane series has increased, because they have a wide range of biological activity, and in addition are donors of nitric oxide. In the scientific literature, many works are related to the synthesis and study of the biological activity of 5-nitro-4,6-dichlorobenzofuroxane amino derivatives, whereas amino derivatives of the 5,7-dichlor-4,6-dinitrobenzofuroxane substrate have been poorly studied.Aim. Is the synthesis of new amino derivatives of 5,7-dichloro-4,6-dinitrobenzofuroxane and the study of their biological activity.Materials and methods. Investigated the reaction of condensation of 5,7-dichloro-4,6-dinitrobenzofuroxane with different aromatic amines, containing functional groups of acceptor character in their structure were selected. In order to increase the yield for each specific reaction, the reaction conditions were selected (the reaction temperature, medium, and the amount of amine). The structure of the compounds confirmed IR, NMR spectra and elemental analysis.Results and discussion. New compounds in the 5,7-diamino-4,6-dinitrobenzofuroxane series were obtained. Acute toxicity, acaricidal and bacteriostatic activity against Escherichia coli and Staphylococcus aureus were studied. The obtained compounds were found to have high pharmacological activity, superior to the comparison drug (Chlorophos and Creolin).Conclusion. Most of the amino derivative synthesized 5,7-dichloro-4,6-dinitrobenzofuroxane have a high activity against mites and bacteria. Compounds containing in their structure chlorine and methyl radicals, have biological activity at low concentrations, are low-toxic and belong to the 4th hazard class.